Receiver tube heat transfer analysis of a CCP collector designed based on branched fractals geometry - Palacios, Angélica; Amaya, Darío; Ramos, Olga (International Journal of Agricultural and Biological Engineering, 2020)
For the development of systems related to renewable energy and specifically for thermo-solar energy, it is essential to study and analyze the different thermal phenomena of heat transfer, in search of the best conditions that allow strengthening the designs. Phenomena such as radiation, convection, and conduction are highly studied, from the field of materials to the field of infrastructure, finding day to day optimal solutions that guarantee a great use of the solar resource available on the earth's surface. This study presented the results of heat transfer analysis on a receiver pipe in a CCP; designed using the theory of branched fractal geometry to improve the heat transfer associated with concentrating solar capture systems. A fractal structure as a branch or arboreal fractal type network, influenced thermal and electrical parameters, as electrical resistance, thermal resistance, and convective heat transfer, so increasing the level branch heat transfer can be enhancement along of the pipe. The use of renewable energies in agriculture benefits the industrial processes that require a continuous power system, due to climatic conditions and geographical location is not a guarantee in food production fields, which reason solar capture systems contribute to food dehydration processes, water heating, refrigeration, and energy production.Keywords: heat transfer, fractal geometry, solar collector, fractality, fractal dimension, parabolic cylindrical concentrator, DOI: 10.25165/j.ijabe.20201305.4733Citation: Palacios A, Amaya D, Ramos O. Receiver tube heat transfer analysis of a CCP collector designed based on branched fractals geometry. Int J Agric & Biol Eng, 2020; 13(5): 56–62.